Appropriate technology in civil engineering proceedings of the conference held by the Institution of Civil Engineers, 14-16 April, 1980. (Thomas Telford, 1981)
Papers in this conference are grouped by the following sessions: 'Roads and Transportation', 'Water Supply and Sanitation', 'Buildings', 'Alternative Energy', 'Irrigation', and 'Management and Planning'.